Coloring substances and adulterants of confectionery - Lewis, Adah (My University, 1907)
Introduction: At the present day when the amount of confectionery consumed by the people of America, both young and old, is somewhat appalling, a great many detrimental effects upon the human system might be avoided if more thought were given to the composition of these delectable but in many cases impure sweets. The highly colored candies which catch the eye of the most frequent candy buyer - the small child - are sometimes the medium for introducing into the child's system the most deadly poison. There are few of us who have reached mature years, but can remember our school days when every tooth in our heads seemed to be the proverbial "sweet-tooth," crying aloud for fuel to feed our rapidly growing bodies. It was then with penny in hand, we stood on tiptoe at some confectioner's counter, and surveyed the tempting array displayed therein, and after much parleying as to how much of this and how much of that we would receive for our cherished penny, we at length decided in favor of the beautiful scarlet "red hots," chiefly because of their brilliant color. Children in general, have the impression that the more highly colored a confection is, the better it will, taste. While harmless coloring substances are used for the most part in the manufacture of confectionery, occasionally a dye is used which might prove harmful if the child consumed a large amount of the candy containing it. The mineral dyes constitute the majority of injurious coloring substances, but fortunately these are being replaced largely by the harmless organic dyes.
Citation: Lewis, Adah. Coloring substances and adulterants of confectionery. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Food Dye; Diet; Colored Substances; Candy; Theses